2014
DOI: 10.1002/acr.22115
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Primary Sjögren's Syndrome in a French Multiracial/Multiethnic Area

Abstract: Compared to subjects with European backgrounds, those with non-European backgrounds had 2.1-2.3 times higher primary SS prevalence and were younger (P < 0.0001) and were more likely to have polyclonal hypergammaglobulinemia (P < 0.0001) and anti-SSA/SSB antibodies (P ‫؍‬ 0.0005 and P < 0.0001 for the AECG and enlarged criteria, respectively). Conclusion. The figure of 1.02-1.52 cases per 10,000 adults we found and estimates from the few other population-based census surveys support that the prevalence of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
2
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 44 publications
9
64
2
9
Order By: Relevance
“…In total, 7 of 18 studies regarding the prevalence of pSS fulfilled ‘good’ quality criteria 13 14 16–19 29. The other 11 studies were designed as sample surveys in which patients with pSS were initially found through questionnaires and then diagnosed using clinical examination based on established diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 7 of 18 studies regarding the prevalence of pSS fulfilled ‘good’ quality criteria 13 14 16–19 29. The other 11 studies were designed as sample surveys in which patients with pSS were initially found through questionnaires and then diagnosed using clinical examination based on established diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, characteristic features are sicca symptoms, including dry eyes and dry mouth [3]. The prevalence of SS has been shown to be between 0.01% and 0.6% [4][5][6]. Several reasons for this variation have been identified, including the use of different classification criteria, selection bias, and whether the study is of a population-based cohort or represents hospital case series [7].…”
Section: Introductionmentioning
confidence: 97%
“…SS predominantly affects middleaged women, with a reported incidence of 3-11 cases per 100,000 persons and a reported prevalence between 0.01 and 0.72% [5][6][7] . Just recently, the first evidence of a strong influence of geolocation and ethnicity on the phenotype of primary SS at diagnosis was reported.…”
Section: Sjögren Syndromementioning
confidence: 99%